0961 Sleep Problems Mediate the Impact of Emotion Regulation on Suicide Ideation. (27th April 2018) - Hartwig, E M; Palmer, C; Rufino, K; Alfano, C; Patriquin, M
Abstract: Introduction: Patients with Major Depressive Disorder (MDD) and Generalized Anxiety Disorder (GAD) are at high risk for suicide. Research suggests this may be due to poor emotion regulation. As sleep problems are a common diagnostic feature of MDD and GAD, this study examined how sleep problems contribute to the relationship between emotion regulation and suicide ideation among inpatient psychiatric patients with and without these disorders. Methods: Participants were 2, 807 inpatients in a psychiatric hospital between 17–89 years old (47.7% female). At admission, a clinical interview determined diagnoses (MDD=945, GAD=192, comorbid MDD/GAD=346, patient control without MDD/GAD=1324) and the Difficulties in Emotion Regulation Scale was measured. Sleep problems were assessed 2 weeks after admission using one item on the Patient Health Questionnaire-9. Suicide ideation was assessed at discharge using the Columbia Suicide Severity Rating Scale. Results: In the MDD group, controlling for age and gender, dysregulated emotion at admission predicted greater suicidal ideation at discharge (B=.04, SE=.01, 95% CI: .02, .05) and more sleep problems during treatment (B=.01, SE=.002, 95% CI: .005, .011). Sleep problems during treatment, in turn, predicted greater suicidal ideation at discharge (B=.59, SE=.16, 95% CI: .27, .91). Results were similar for the patient control group. Significant indirect effects revealed sleep problems partially explained the relations between emotion regulation and suicide ideation for both the MDD (B=.005, SE=.002, 95% CI: .002, .008) and patient control groups (B=.007, SE=.002, 95% CI: .004, .01). No significant effects were found for the GAD or comorbid MDD/GAD groups. Conclusion: Sleep problems mediate the relationship between emotion regulation and suicide ideation in most patients, but the presence of GAD in the diagnostic profile is associated with differential relationships between these symptoms. Sleep problems are modifiable, and future research should examine sleep problems as a treatment target among those at-risk for suicide. Support (If Any): N/A.